Highly Superior Autobiographical Memory: Quality and Quantity of Retention Over Time - LePort, Aurora K. R.; Stark, Shauna M.; McGaugh, James L.; Stark, Craig E. L. (Frontiers in Psychology, 2016)
Individuals who have Highly Superior Autobiographical Memory (HSAM) are able to recall, with considerable accuracy, details of daily experiences that occurred over many previous decades. The present study parametrically investigates the quantity and quality of details of autobiographical memories acquired 1-week, 1-month, 1-year, and 10-years prior in HSAMs and controls. In addition, we tested the consistency of details provided at the 1-week delay by testing the subjects 1 month later with a surprise assessment. At the 1-week delay, HSAMs and controls recalled an equivalent number of events. In contrast, HSAM recall performance was superior at more remote delays, with remarkable consistency following a 1-month delay. Further, we revealed a relationship between the consistency of recall and HSAMs’ obsessive–compulsive tendencies. These data suggest that HSAMs experience normal encoding, yet enhanced consolidation and later recall of autobiographical events.